Financial Satisfaction and Psychological in Different Demographic Characteristics - Fahmi, Ranip; Faturohman, Taufik (Granada El-Fath, 2024)
This study analyzes Subjective Well-Being (SWB), comprising Financial Satisfaction and Psychological Well-Being, among productive young adults aged 18–35 in Indonesia. It evaluates the influence of demographic factors such as gender, age, employment status, education level, income, and expenses on SWB. Data were collected through an online questionnaire using a six-point Likert scale, with 344 valid responses from a total of 347 respondents. The findings reveal that males have higher SWB compared to females. Respondents aged 26–35 reported the highest financial satisfaction, while those aged 18–25 showed the best psychological well-being. Full-time workers and individuals with higher education levels reported the highest SWB. Additionally, incomes exceeding IDR 10,000,000 and controlled expenses positively contributed to SWB. This study recommends financial literacy programs and accessible mental health services to reduce financial stress and improve the well-being of Indonesia's young adults.